Identification of Morpho-Physiological and Yield Traits of Sweet Corn Hybrids at Various Shade Levels - Endah Dwi Susanti; Muhamad Achmad Chozin; Arya Widura Ritonga; Dwiwanti Sulistyowati (Caraka Tani: Journal of Sustainable Agriculture, 2023)
The selection of shade-tolerant sweet corn under intercropping conditions is necessary to provide adaptive superior cultivars for agroforestry systems. Until recently, there have not been many reports of superior varieties of sweet corn tolerant to low light. This study aimed to determine the differences in the morphological, physiological and production responses of 25 hybrid sweet corn genotypes to low light intensity. This study used a nested design with three replications. The factors tested were the shade level (0%, 25%, 50% and 75%) and the genotype of hybrid corn. The results showed that most of the hybrid corn genotypes tested showed an increase in production at 25% shade, while at 50% and 75% shade, they showed a decrease in production. Based on relative production at 25% shade, the genotypes can be split into three groups: sensitive, moderate and tolerant. The tolerant genotype including F1 T8-2A x SM12-2 (G6); Exotic (G13); Talenta (G15); Golden boy (G16); F1 SM12-2 x T9-2 (G20) provided the highest increase in morpho-physiological characters and yields compared to the moderate and sensitive. In all genotype groups, morphological variables (number of leaves, leaf area, stem diameter and relative growth rate), physiological variables (stomata conductance, photosynthetic rate, and total dissolved solids (TDS)), and yield variables (length, diameter, number, weight and unhusked weight of ears) were significantly higher in the no-shade than in the shaded conditions. These findings can be used as a basis for sweet corn planting recommendations under shade condition areas such as in agroforestry systems.